Dendrogram Zonasi Pertumbuhan Mangrove Berdasarkan Habitatnya di Kawasan Rehabilitasi Pantai Utara Jawa Tengah Bagian Barat - Erny Poedjirahajoe (Fakultas Kehutanan Universitas Gadjah Mada, 2007)
Dendrogram Zoning of Mangrove Growth Based on Its Habitat in the Rehabilitation Area on the North Coasts, West Region of Central JavaThe growth of rehabilitated mangrove, although planted at the same time, shows differences in terms of density and height growth. Such condition is visible in the North Shore of Brebes, Tegal and Pemalang Regency.The research result shows that mangrove growth planted in 2001 on the North Shore of Brebes, Tegal and Pemalang Regency is not apart from several factors, among others are its habitat physical-chemical factors. The result of regression correlation analysis shows that the habitat factors which play an important role in the vegetation density are salinity, temperature and plankton population. Meanwhile, the most dominant factor which determines the vegetation height growth is salinity and phosphor. The combination role based on its habitat shows that mangrove growth in Brebes Regency on proximal (1P) and medial (1M) zone and the one in Pemalang Regency on proximal zone (3P) has the shortest cluster, so that those research locations have similarity on vegetation growth and its habitat factors. Meanwhile, the proximal (2P) zone in Tegal Regency is similar with the medial (2M) zone. Mangrove growth on distal zone in Tegal Regency has less good growth parameter and habitat factors compared to that of in Brebes and Pemalang for containing more sand.From the research result, it can be concluded that the existence of habitat factors salinity, plankton population and phosphor have to be taken into consideration if a mangrove area will be rehabilitated/planted especially using Rhizophora mucronata seedlings. In order to reach the maximum achievement, one thing which has to be taken into consideration is the habitat clustering of the planted area, especially in Brebes, Tegal and Pemalang Regency area.